The Piotroski F-Score: A fundamental value strategy revisited from an investor's perspective - Christopher Krauss; Tom Krüger; Daniel Beerstecher (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2015)
This paper revisits the Piotroski F-score strategy in the U.S. stock universe from an investor's perspective. Primarily, we aim to answer the question, whether the high abnormal returns of more than 20 percent p.a. previously proclaimed by academics (Piotroski, 2000) and practitioners (AAII, 2015) can be feasibly captured by individual or professional investors. As such, our focal point is a pragmatic approach an average investor could opt for as well. We use the software Stock Investor Pro from the American Association of Individual Investors to obtain screenshots of the U.S. stock universe from 2005-2015 on a weekly basis. Next, we devise a long-only and a long-short variant of the Piotroski strategy with monthly or weekly rebalancing frequencies. At first glance, our findings re-confirm the high returns of this fundamental value strategy. Specifically, the monthly (weekly) long-only strategy generates raw returns of 30.93 (65.41) percent p.a. These returns outperform relevant benchmark indices and can only partially be explained by common systematic risk factors. However, consideration of liquidity constraints and an estimate of trading costs in this low liquidity stock universe render both strategies virtually unprofitable. Nevertheless, there may be potential for further research aiming at implementing such a strategy on more liquid investment universes.
Keywords: 330; Piotroski F-score; value investing; financial statement analysis; high-book-to-market; stock screening; fundamental analysis